2019
DOI: 10.1101/611301
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How Cognitive and Affective Empathy Relate to Emotion Regulation: Divergent Patterns from Trait and Task-Based Measures

Abstract: Evidence suggests that empathy and emotion regulation may be related, but few studies have directly investigated this relationship. Here we report two experiments which examined: 1) how different components of empathy (cognitive & affective) relate to the habitual use of cognitive reappraisal to regulate emotions (N=220), and 2) how these components of empathy relate to implicit reappraisal in a context-framing task (N=92). In study 1, a positive correlation between cognitive empathy and reappraisal use was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 74 publications
(111 reference statements)
1
12
0
Order By: Relevance
“…Emotion suppression showed no association with any of the QCAE factors. Consistent with our findings, past studies have shown positive associations for cognitive reappraisal with cognitive empathy [ 46 49 ]; and also, no association [ 46 , 49 ] with affective empathy. In the case of emotion suppression, past findings have also shown no association [ 47 , 48 ] with cognitive and affective empathy [ 46 , 47 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Emotion suppression showed no association with any of the QCAE factors. Consistent with our findings, past studies have shown positive associations for cognitive reappraisal with cognitive empathy [ 46 49 ]; and also, no association [ 46 , 49 ] with affective empathy. In the case of emotion suppression, past findings have also shown no association [ 47 , 48 ] with cognitive and affective empathy [ 46 , 47 ].…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, emotion suppression may be dysfunctional [ 42 , 43 ], and associated with negative social outcomes [ 44 , 45 ]. Past studies have shown positive associations for cognitive reappraisal with cognitive empathy [ 46 49 ]; and also, no association [ 46 , 49 ] or negative association [ 47 , 48 ] with affective empathy. In the case of emotion suppression, past findings have shown that it has either no association [ 47 , 48 ] or positive association [ 46 ] with cognitive empathy.…”
Section: Introductionmentioning
confidence: 99%
“…Participants filled in the Interpersonal Reactivity Index online to assess empathy, which is closely related to the individual's processing of the unpleasant pictures and CR sentences (Thompson et al, 2019). One day later, they came to the laboratory.…”
Section: Figurementioning
confidence: 99%
“…Being able to understand other people's emotions, to feel with them and show compassion, that is, our socioaffective and sociocognitive processes, is important for successful and satisfying social interactions. Notably, there is growing evidence that social cognitive-affective processes and emotion regulation are interrelated (Thompson, van Reekum, & Chakrabarti, 2019;Thompson, Uusberg, et al, 2019). More concretely, our response to another person's emotions may differ depending on our ability to regulate our emotional states (Gross, 1998;McRae & Gross, 2020).…”
Section: Psychological Science Theoretical/methodological/review Articlementioning
confidence: 99%
“…Findings from studies of adaptive emotion regulation and cognitive empathy support these assumptions: For example, a study by Laghi et al (2018) with adolescents found that cognitive reappraisal is positively linked to perspective taking. For nonclinical participants, moderate (Buruck et al, 2014;Jordan et al, 2002;Powell, 2018;Shaw et al, 2020;Thompson, van Reekum, & Chakrabarti, 2019;Tully et al, 2016;Wang et al, 2017) to high (Berrios Martos et al, 2013;Taute et al, 2010) positive correlations have been found between adaptive emotion regulation and cognitive empathic abilities. However, in clinical samples, this link vanishes (Ghiasi et al, 2016;Lehmann et al, 2014;Rowland et al, 2013), perhaps because these samples typically use adaptive emotion regulation less frequently than nonclinical samples do (Aldao et al, 2010).…”
Section: The Relationship Between Emotion Regulation and Cognitive Em...mentioning
confidence: 97%